2014
DOI: 10.1371/journal.pone.0103988
|View full text |Cite|
|
Sign up to set email alerts
|

Ovarian Cancer Cell Line Panel (OCCP): Clinical Importance of In Vitro Morphological Subtypes

Abstract: Epithelial ovarian cancer is a highly heterogeneous disease and remains the most lethal gynaecological malignancy in the Western world. Therapeutic approaches need to account for inter-patient and intra-tumoural heterogeneity and detailed characterization of in vitro models representing the different histological and molecular ovarian cancer subtypes is critical to enable reliable preclinical testing. There are approximately 100 publicly available ovarian cancer cell lines but their cellular and molecular char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
395
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(425 citation statements)
references
References 74 publications
27
395
1
2
Order By: Relevance
“…Accordingly, precision oncology depends on the ability to functionally interrogate preclinical models capturing the molecular heterogeneity observed in patients. While collections of cancer cells derived from multiple tumor types have been previously described 1,2,4 , comprehensive databases of cells derived from single tumour lineages are much less common 16,31 . To capture the clinical heterogeneity of CRCs, we assembled a collection of 151 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, precision oncology depends on the ability to functionally interrogate preclinical models capturing the molecular heterogeneity observed in patients. While collections of cancer cells derived from multiple tumor types have been previously described 1,2,4 , comprehensive databases of cells derived from single tumour lineages are much less common 16,31 . To capture the clinical heterogeneity of CRCs, we assembled a collection of 151 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The ovarian carcinoma cell line A2780 and the uterine sarcoma cell line MES-SA were compared to their doxorubicin-selected counterparts A2780adr and MES-SA/Dx5, respectively [57][58][59], while the cervix carcinoma cell line KB-3-1 was compared to the vinblastine-selected line KB-V1 [60,61]. In addition, toxicity of selected active derivatives M A N U S C R I P T…”
Section: Assessment Of Cytotoxicity In An Mdr Cell Panelmentioning
confidence: 99%
“…The largest effect in Wang et al (14) study was observed after 120 h incubation with IL-6, IL-8 or both. Additionally, the cell lines used were different in origin, genetic profile and clinical stage, so the influence of IL-6 and IL-8 may be different (15).…”
Section: Discussionmentioning
confidence: 99%